Agents and artificial intelligence : Third International Conference, ICAART 2011, Rome, Italy, January, 28-30, 2011. Revised Selected Papers - Fred, Ana; Filipe, Joaquim (Communications in Computer and Information Science, 2013)
This book constitutes the thoroughly refereed post-conference proceedings of the Third International Conference on Agents and Artificial Intelligence, ICAART 2011, held in Rome, Italy, in January 2011. The 26 revised full papers presented together with two invited paper were carefully reviewed and selected from 367 submissions. The papers are organized in two topical sections on artificial intelligence and on agents.